Optimizing pre-match preparation: Impact of four warm-up protocols on yo-yo IR2 and sprint performance in youth footballers - Isbilir, M.; Ispirlidis, I.; Chatzinikolaou, A.; Pafis, G.; Gioftsidou, A. (Journal of Physical Education and Sport, 2025)
Problem Statement: Warm-up routines are crucial for enhancing athletic performance and minimizing injury risk, particularly in sports that involve explosive movements, such as soccer. Although various traditional and innovative warm-up strategies have been studied, there is a lack of systematic comparison among multiple protocols that integrate equipment such as foam rollers, resistance bands, and other balancing equipment to evaluate their effects on key performance measures in young athletes. Approach: This study employed a randomized crossover experimental design to investigate the effects of four distinct warm-up protocols on sprint performance (10 and 30 m) and endurance (Yo-Yo Intermittent Recovery Test Level 2) in 20 male elite U17 football players from the Greek National League. Each 30-minute protocol includes combined activation exercises, dynamic movements, resistance drills, and sport-specific activities to analyze their relative effectiveness. We conduct performance tests following a standardised 15-minute rest period, simulating pre match conditions. Purpose: This research aimed to evaluate how distinct warm-up strategies affect short-term sprint and endurance performance, providing evidence-based recommendations for optimizing pre-match preparation in youth football. Results: Analysis revealed no significant differences in Yo-Yo IR2 performance across the four protocols (p =.957). However, significant differences were observed in 10 m (p =.000) and 30 m sprint times (p =.000). Protocol 1 (activation warm-up with foam rollers, resistance bands, BOSU ball, and football-specific drills) and Protocol 2 (dynamic warm-up and football-specific drills) yielded superior performance in sprint times compared to protocols involving higher resistance loading (Protocols 3 and 4), which negatively impacted sprint outcomes, likely due to increased muscle fatigue. Conclusions: Dynamic and activation-based warm-up routines that balance neuromuscular activation and fatigue appear more effective for optimizing sprint performance without compromising endurance. In contrast, warm-ups emphasizing resistance based exercises may impair short-term explosive performance due to fatigue-related mechanisms. Coaches and practitioners should carefully tailor warm-up routines to match sport-specific demands while minimizing pre competition fatigue, particularly in youth athletes.